Clock & compass : how John Byron Plato gave farmers a real address - Monmonier, Mark S. (University of Iowa Press, 2022)
"A city guy who aspired to be a farmer, John Byron Plato took a three-month winter course in agriculture at Cornell before starting high school, which he left a year before graduation to fight with US troops during the Spanish-American War. After the war he worked as a draftsman, ran a veneers business, patented and manufactured a parking brake for horse-drawn delivery wagons, taught school, and ran a lumber yard. In his early thirties he bought some farmland north of Denver and began raising Guernsey cattle, which he advertised for sale in the local paper. When an interested buyer eager to see his calves couldn't find his farm, Plato realized that an RFD postal address was only good for delivering mail. Farmers had started buying cars and trucks, but without adequate maps and signage townsfolk couldn't visit them and they couldn't easily find each other. Plato's solution was a map-and-directory combo that used direction and distance from a local business center to give farmers a real address, just like city folk. He patented his invention and tried to sell it to the Post Office, which took a pass-their business was delivering mail, not facilitating travel. Because the clockface's hours provided the directions, he called his strategy the "Clock System." Some Chicago promoters became intrigued but after their plans failed to gel, he decided to produce the maps himself. Rural sociologists at Cornell, who considered the Clock System an antidote for rural isolation, encouraged him to start a business in Ithaca, where he mapped a dozen New York counties until the Great Depression intervened and he left to work as a government mapmaker in Washington. Between 1936 (after his patent had expired) and 1940, some Ithaca businessmen validated the concept by making "Compass System" maps for half the state's counties"--